2022
DOI: 10.32649/ajas.2022.176567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Different Levels of Canola Oil on the Hematological and Biochemical Characteristics of Common Carp Cyprinus Carpio L.

Abstract: The fish production industry has become one of the most important animal production projects, and fish industry suffer from feed costs, so this study aims to find accessible food additives that increase production or reduce costs. This was done by 126 fish of common carp (Cyprinus carpio L.) Average individual weight 42.72 g ± 2.28 g. and 254.78 g ± 2.95 g biomass weight. were randomly distributed to 21 aquaria, with seven treatments with three replicates, 6 fish per aquarium. Fish were fed 3% by weight of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…He et al [22] showed in their study that astaxanthin prevents ovarian aging by improving the antioxidant capacity in the body of laying hens and enhancing the level of production of reproductive hormones, Gao et al [59] who found when adding astaxanthin at a level of 25, 50 and 100 mg/kg feed to the diet of laying hens at the age of 50 weeks led to an improvement in the level of total antioxidant capacity and glutathione peroxidase enzyme in blood plasma and a significant decrease (P<0.05) in blood plasma, the level of malondialdehyde (MDA) compared with the control treatment, and the improvement in these traits increased linearly with increasing the level of astaxanthin to the diet, also the results agreed with Heng et al [49] when adding astaxanthin at levels of 0, 20, 40, 80 and 160 mg/kg feed to the diet of laying hens a significant increase (P<0.05) was found for the coefficients of adding astaxanthin in the level of glutathione peroxidase and a significant decrease (P<0.05) in the level of malondialdehyde in the blood plasma compared with the control treatment, The results also agreed with the findings of Dansou et al [60], as they showed that when adding astaxanthin at levels of 0, 7.1, 14.2, 21.3, and 42.6 mg / kg feed to the laying hens diet, the activity of antioxidant enzymes increased and the level of malondialdehyde (MDA) decreased. They explained the reason this is due to the fact that antioxidants work to modify the enzymatic system in the ovaries by increasing the levels of antioxidant enzymes and reducing programmed cell death in the ovaries by regulating the enzymatic system in the ovaries, also the results agreed with Zhu et al [56] when adding astaxanthin to the diet of laying hens it led to a significant increase (P<0.05) in the level of glutathione peroxidase and catalase in blood plasma, and a significant decrease (P<0.05) in the level of malondialdehyde (MDA) compared with the control treatment.…”
Section: Alt and Ast Enzyme Activity And Indicators Of Oxidative Stre...supporting
confidence: 90%
“…He et al [22] showed in their study that astaxanthin prevents ovarian aging by improving the antioxidant capacity in the body of laying hens and enhancing the level of production of reproductive hormones, Gao et al [59] who found when adding astaxanthin at a level of 25, 50 and 100 mg/kg feed to the diet of laying hens at the age of 50 weeks led to an improvement in the level of total antioxidant capacity and glutathione peroxidase enzyme in blood plasma and a significant decrease (P<0.05) in blood plasma, the level of malondialdehyde (MDA) compared with the control treatment, and the improvement in these traits increased linearly with increasing the level of astaxanthin to the diet, also the results agreed with Heng et al [49] when adding astaxanthin at levels of 0, 20, 40, 80 and 160 mg/kg feed to the diet of laying hens a significant increase (P<0.05) was found for the coefficients of adding astaxanthin in the level of glutathione peroxidase and a significant decrease (P<0.05) in the level of malondialdehyde in the blood plasma compared with the control treatment, The results also agreed with the findings of Dansou et al [60], as they showed that when adding astaxanthin at levels of 0, 7.1, 14.2, 21.3, and 42.6 mg / kg feed to the laying hens diet, the activity of antioxidant enzymes increased and the level of malondialdehyde (MDA) decreased. They explained the reason this is due to the fact that antioxidants work to modify the enzymatic system in the ovaries by increasing the levels of antioxidant enzymes and reducing programmed cell death in the ovaries by regulating the enzymatic system in the ovaries, also the results agreed with Zhu et al [56] when adding astaxanthin to the diet of laying hens it led to a significant increase (P<0.05) in the level of glutathione peroxidase and catalase in blood plasma, and a significant decrease (P<0.05) in the level of malondialdehyde (MDA) compared with the control treatment.…”
Section: Alt and Ast Enzyme Activity And Indicators Of Oxidative Stre...supporting
confidence: 90%